2021
DOI: 10.1007/s00464-021-08497-9
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted laparoscopic inguinal hernia repair after previous transabdominal prostatectomy

Abstract: Background Transabdominal prostatectomy results in scarring of the retropubic space and this might complicate subsequent preperitoneal dissection and mesh placement during minimally invasive inguinal hernia repair. Therefore, it suggested that an open anterior technique should be used rather than a minimally invasive posterior technique in these patients. Methods In this single-center study, a retrospective analysis of a prospectively maintained database w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…No data with regard to patients who had previous prostatectomies were reported in the included studies. Recent papers showed that the robotic platform with its improved dexterity and enhanced high-definition three-dimensional image may be particularly helpful in the challenging dissection of the retro-pubic space in patients who had prior prostatectomies [ 36 , 37 ]. Those advantages offered by the robotic platform may expand the indications for minimally invasive inguinal hernia repair also for those cases which, nowadays, are performed only by expert laparoscopic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…No data with regard to patients who had previous prostatectomies were reported in the included studies. Recent papers showed that the robotic platform with its improved dexterity and enhanced high-definition three-dimensional image may be particularly helpful in the challenging dissection of the retro-pubic space in patients who had prior prostatectomies [ 36 , 37 ]. Those advantages offered by the robotic platform may expand the indications for minimally invasive inguinal hernia repair also for those cases which, nowadays, are performed only by expert laparoscopic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Возможность и безопасность применения минимально инвазивных методик лечения паховых грыж у пациентов с ранее перенесенными операциями на нижних отделах живота, в том числе после радикальной простатэктомии, занимала умы исследователей в течение длительного времени [16]. Результаты исследований, направленных на изучение данной проблемы, позволяют предположить безопасность эндоскопических методик герниопластики в руках высококвалифицированного специалиста, при этом TEP характеризуется относительно большей длительностью вмешательства по сравнению с ТАРР [17,18].…”
Section: №2 (45) 2022unclassified
“…Choosing the best technique for repairing an inguinal hernia is challenging because the available data is controversial. To date, numerous observational studies [5][6][7][8] and one randomized trial have failed to demonstrate that short-term and functional outcomes after robotic surgery are superior to those of laparoscopic surgery for patients with inguinal hernia. The aim of the review is to provide an overview about the current practice for inguinal hernia repair with the focus on robotic approach.…”
Section: Robotic-assisted Inguinal Hernia Repair: a Historical Reviewmentioning
confidence: 99%